INNOVATIVE PEDAGOGICAL IN TECHNOLOGY TEACHING USE OF TECHNOLOGIES - Nabiyeva Zamirakhan; Ashurova Umida Khan (Journals Park Publishing, 2023)
This article describes the use of innovative pedagogical technologies in teaching technology in general secondary schools, the formation of technical creativity in young students.
Keywords: Technology, intellectual projects, creativity, rationalization, invention.